THEORETICAL IMPACT OF ENHANCED MUSHARAKAH MUTANAQISAH HOME FINANCING ON REAL ESTATE PRICES - Asadov, Alam I.; Ibrahim, Mansor H. (Bank Indonesia, 2018)
This paper theoretically analyzes two alternative modes of home financing. The first mode is the conventional housing loan and the other is Enhanced Musharakah Mutanaqisah (EMM) home financing. Our results reveal the EMM based setting is superior to the conventional housing loans in at least two aspects. These are the prevention of house price inflation in all phases of economic business cycle and the smoothening of real estate cycles. This means that, under the EMM, the risk of real estate bubble formation is subdued, which should prove to be welfare improving.